The history of al Tabari - The_history... (State University of New York Press, 1989)
ir, Jil.1-13=c.1 ; jil.14=c.1-2 ; Jil.15-36=c.1 ; Jil.38-39=c.1/ast, jil.3,13,20 =c.2/stoc6=jil.35c.2/stc13,jil.37,c.1